Variation in Water Masses on Shelf of Northern Bering Sea in September 2016-2018. Issue 3 (3rd May 2020) - Wang, Yingjie; Liu, Na; Lin, Lina; He, Yan; Kong, Bin; Zhang, Zhanhai
Abstract: Based on hydrological data obtained during the 7th to 9th Chinese National Arctic Research Expeditions in the summers of 2016–2018, the main water structure on the shelf of the northern Bering Sea and the volume and heat fluxes of the Bering Strait throughflow were analyzed. Distinct variability was identified in the three Pacific water masses feeding the strait - Anadyr Water (AW), Bering Shelf Water (BSW) and Alaskan coastal water (ACW). Overall, the temperature and salinity of the entire section increased each year, with 2018 showing significant anomalies, i.e., a temperature anomaly of up to 1 °C and a maximum salinity anomaly of 2. From 2016 to 2018, the extent of the ACW gradually narrowed in the eastern part of this section, while the AW expanded eastward each year. The net volume transport through each of the three sections increased poleward from 1.65 Sv to 2.76 Sv, with the AW increasing from 0 Sv to 1.03 Sv, the BSW varying between 0.52–1.65 Sv, and the ACW gradually decreasing from 1.04 Sv to disappearing completely. The net heat fluxes were also poleward, varying between 25.77 TW and 61.50 TW, and showing a significant increase. Significant variations in magnitude and extent were observed in each water mass of the Bering Strait throughflow, which could produce widespread effects in the Arctic Ocean and the global ocean beyond.